Investigations on the efficiency variation of zinc and gallium Co-doped TiO2 based dye sensitized solar cells. Issue 16 (November 2020) - Khan, M.I.; Hassan, Ghulam; Hasan, M.S.; Abubshait, Samar A.; Abubshait, Haya A; Al-Masry, Waheed; Mahmood, Q.; Mahmood, Asif; Ramay, Shahid M.
Abstract: In this research the electric performances of Dye Sensitized Solar Cells (DSSCs) using titanium dioxide (TiO2 ) photoanodesco-doped with 1% Zn & (0%, 0.5%, 1% and 1.5%) Ga has been investigated. The films of undoped and co-doped TiO2 have been deposited by sol gel dip coating technique. The structure and optical properties of pure and 1% Zn & (0%, 0.5%, 1% and 1.5%) Ga co-doped TiO2 films are investigated. XRD spectra reveal that studied films hasanatase tetragonal structure of TiO2 with a small shifting angle when the doping percentages of Zn and Gaare increased. The crystallites have an average size in the range of 11–18 nm. Calculated lattice parameters are well matched with the reported value. a-axis remains same with doping while c-axis varies with doping. UV–Vis spectroscopy results show that band gap energy (Eg ) is decreased with doping. Maximum decrease in Eg is found at the doping percentage of 1% Zn and 1% Ga and value is 3.20 eV. The efficiency of realized DSSC is increased considerably compared to that using pure TiO2 photoanode. The current versus voltage (I–V) characteristics reveal that the DSSC prepared using 1% Zn & 1% Ga co-doped TiO2 layer has significantly improved parameters. This cell has a high power conversion efficiency of 4.36%, short current density of 7.24 mA/cm 2 and open circuit voltage of 0.86 V.